Dynamics of photodoped charge transfer insulators - Golez, Denis; Boehnke, Lewin; Eckstein, Martin; Werner, Philipp (Physical Review B, 2019)
We study the dynamics of charge transfer insulators after photoexcitation using the three-band Emery model and a nonequilibrium extension of Hartree-Fock + EDMFT (extended dynamical mean field theory) and GW + EDMFT. While the equilibrium properties are accurately reproduced by the Hartree-Fock treatment of the ligand bands, dynamical correlations are essential for a proper description of the photodoped state. Photodoping leads to a renormalization of the charge transfer gap and to a substantial broadening of the bands. We calculate the time-resolved photoemission spectrum and optical conductivity and find qualitative agreement with experiments. Our formalism enables the realistic description of nonequilibrium phenomena in materials with ligand bands. It provides a tool to explore the optical manipulation of interaction and correlation effects, including insulator-metal and magnetic transitions.
CRIS-Team WoS Importer:2019-08-02